Bez imena i znaka - Bošković, Dragan (Slavistična revija, 2013)
By abolishing the conventional humanistic reading code, the paper seeks to suggest that the thanatophilian identity of the sign/bridge is prevailing in Ivo Andrićs works, and hence their mainstream ideological semantics should be re-examined in terms of the ontological identity of death. Contrary to the interpretation of the bridge as an aesthetic, ethno- or geo-historical, even economic ideologeme, the author offers an interpretation of the bridge as the unbridgeable, the face of death, a headstone, a crack in a sign. The crack in a sign corresponds to the crack in the subject through which the death is announced as a source of signifying, narration, art, and socio-political identity. The possibility of escape from that kind of logic is concealed in heroes who end up in madness, in semantic dissymmetry, thus becoming the bridges leading toward the alternate, ontological territories of Otherness.
Keywords: "Most na Žepi"; "Na Drini ćuprija"; Andrić, Ivo, 1892-1975; bridge; death; most; nihilism; nihilizem; Serbian literature; smrt; srbska književnost